Aromaterapi Sebagai Terapi Komplementer untuk Mengatasi Nyeri, Depresi, Mual dan Muntah pada Pasien Kanker: A Literature Review - nuriya; Galih Noor Alivian; Agis Taufik (Journal of Bionursing, 2021)
Introduction: Cancer is an abnormal cell growth that attacks the surrounding tissue which can cause death for the sufferer. Cancer is the second leading cause of death in the world by 13% after cardiovascular disease. Cancer can cause sufferers to experience a decrease in physical conditions such as pain and psychologically such as depression. One of the pharmacological therapies that can cure cancer is chemotherapy. Chemotherapy has side effects of myelosuppression, nausea and vomiting, causing discomfort for the sufferer. One of the complementary therapies that can reduce pain, depression and the effects of chemotherapy is aromatherapy. Methods: This study used 6 steps including, formulating research questions and objectives, searching for existing literature, screening according to inclusion, assessing article quality, extracting data, and analyzing data. Articles obtained from data based on Google Scholar. Using Indonesian keywords, namely: “Aromatherapy”, “Nausea”, “Vomiting”, “Cancer”, “Pain”, there were 5 articles that met the inclusion criteria and were included in the analysis. Results: Aromatherapy has been shown to be effective in reducing pain and depression in cancer patients as well as providing comfort to reduce nausea and vomiting due to the effects of chemotherapy administered by patients. Discussion: Complementary aromatherapy interventions have good benefits for cancer patients in reducing pain and depression and reducing nausea and vomiting. The provision of this therapy should be promoted more widely to patients and health professionals to support patient comfort. Conclusion: Aromatherapy can reduce pain and depression and reduce nausea and vomiting in cancer patients undergoing chemotherapy.